Mortality among autoworkers manufacturing electronics in Huntsville, Alabama. Issue 4 (19th December 2018) - DeBono, Nathan; Kelly‐Reif, Kaitlin; Richardson, David; Keil, Alex; Robinson, Whitney; Troester, Melissa; Marshall, Stephen
Abstract : Background: Workers raised concerns over suspected excesses of mortality at automotive electronics manufacturing facilities in Huntsville, Alabama. Methods: A study of 4396 UAW members ever‐employed at Huntsville facilities between 1972 and 1993 was conducted with mortality follow‐up through 2016. Standardized Mortality Ratios (SMRs) were estimated using U.S. and Alabama reference rates. Results: Relative to U.S. rates, there was a modest excess of all‐cause mortality among White female workers (SMR 1.08, 95%CI: 0.99‐1.18) and among all workers hired <1977 at the original plant building (SMR 1.10, 95%CI: 0.99‐1.22). There was excess nervous system disorder (SMR 1.24, 95%CI: 0.91‐1.65) and brain and nervous system cancer (SMR 1.31, 95%CI: 0.67‐2.28) mortality. Estimates for several causes of interest were imprecise. Conclusions: All‐cause mortality estimates were greater than anticipated based on results from other UAW cohorts. The excess of nervous system disease mortality is consistent with other studies of electronics workers exposed to lead‐solder and chlorinated solvents.